Biodiritto e Unione Europea: primi spunti di riflessione (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The article aims to deepen the relationship between biolaw and European Union law, in order to understand what role the latter plays in the regulation of issues characterized by a high level of scientific and ethical complexity. Having identified a dual legal basis for the emergence of a European biolaw – the protection of the European common market (Article 114 TFEU) and the promotion of health (Article 168 TFEU) – the progressive emergence of an axiological, and not only procedural, dimension will be highlighted assuming the case-law of the Court of Justice as a common thread.
Keywords: Biolaw; European Union; Court of Justice; scientific data; integration